Antioxidant, Antimicrobial, and Anticancer Effects of Anacardium Plants: An Ethnopharmacological Perspective - Salehi, Bahare; Gültekin-Özgüven, Mine; Kirkin, Celale; Özçelik, Beraat; Morais-Braga, Maria Flaviana Bezerra; Carneiro, Joara Nalyda Pereira; Bezerra, Camila Fonseca; Silva, Teresinha Gonçalves da; Coutinho, Henrique Douglas Melo; Amina, Benabdallah; Armstrong, Lorene; Selamoglu, Zeliha; et al. (Frontiers in Endocrinology, 2020)
Anacardium plants have received increasing recognition due to its nutritional and biological properties. A number of secondary metabolites are present in its leaves, fruits, and other parts of the plant. Among the diverse Anacardium plants' bioactive effects, their antioxidant, antimicrobial, and anticancer activities comprise those that have gained more attention. Thus, the present article aims to review the Anacardium plants' biological effects. A special emphasis is also given to their pharmacological and clinical efficacy, which may trigger further studies on their therapeutic properties with clinical trials.